RECENT RESULTS IN NEUTRINO PHYSICS - Naumov, D. V. (Одеські астрономічні публікації, 2011)
This manuscript is a shorthand version of my talk given at Odessa Gamov School on Astronomy, Cosmology and Beyond (22-28 August 2011, Odessa, Ukraine). Within this note we very briefly review the main achievements, new results and open problems in neutrino physics of today.